Cholera: a Potential Threat to the Sanitary and Epidemiological Well-Being of the Population of the Republic of Tajikistan - A. V. Ivanova; Z. G. Gulmakhmadzoda; E. A. Chumachkova; A. A. Zubova; K. M. Azizov; Z. O. Kadamov; F. F. Maksumova; Ya. A. Neishtadt; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2025)
Cholera remains a topical issue for global health, including for non-endemic countries in the context of cross-border spread. Intra-, interstate and intercontinental migration of the population, which plays a major role in the genesis of outbreaks and epidemics on various continents, continues to determine the epidemiological risks of cholera importation to different countries of the world. The paper considers the current risks of cholera introduction into the territory of the Republic of Tajikistan, primarily related to the possibility of cross-border import from Afghanistan, where cholera outbreaks are recorded annually, due to the extended common border (1,357 km). Internal risks to the sanitary and epidemiological well-being of the country’s population contributing to the spread of infection in case of importation have been identified. Among them, the following factors deserve special attention: the presence of climatic conditions favorable for the existence of cholera vibrio, limited sanitary and hygienic capacities of the preventive service, and an annual increase in migration flows, both inside and outside the country. The paper presents the current epidemiological situation on acute intestinal infections in the areas bordering Afghanistan in the Khatlon Region of the Republic of Tajikistan. The territories with the most intense epidemiological situation as regards acute intestinal infections have been visualized using geo-information analysis. In addition, it has been established that there is a high probability of infection importation from countries affected by cholera. The mechanisms for solving the issues of effective and prompt response to the complication of the epidemiological situation on cholera in the event of its introduction into the territory of the Republic of Tajikistan are put forward: early integrated planning of the organization and implementation of preventive and anti-epidemic measures aligned with all interested agencies of the republic.